2021
DOI: 10.3390/nu13103603
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Cardiovascular Disease: Current Evidence and Future Perspectives

Abstract: Vitamin D deficiency is a prevalent condition, occurring in about 30–50% of the population, observed across all ethnicities and among all age groups. Besides the established role of vitamin D in calcium homeostasis, its deficiency is emerging as a new risk factor for cardiovascular disease (CVD). In particular, several epidemiological and clinical studies have reported a close association between low vitamin D levels and major CVDs, such as coronary artery disease, heart failure, and atrial fibrillation. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 100 publications
1
60
0
2
Order By: Relevance
“…Both nuclear vitamin D receptor (VDR) and the enzyme 25-hydroxyvitamin D3-1αhydroxylase have been identified in various cells of the cardiovascular system, indicating a direct involvement of this hormone group in the initiation and progression of CVD [41]. Importantly, in patients with heart failure, atrial fibrillation, or coronary artery disease vitamin D deficiency was associated with a worse prognosis [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Both nuclear vitamin D receptor (VDR) and the enzyme 25-hydroxyvitamin D3-1αhydroxylase have been identified in various cells of the cardiovascular system, indicating a direct involvement of this hormone group in the initiation and progression of CVD [41]. Importantly, in patients with heart failure, atrial fibrillation, or coronary artery disease vitamin D deficiency was associated with a worse prognosis [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…3 The effects of vitamin D deficiency on atrial fibrillation (AF) are explained by direct effects on atrial tissue and indirect effects on cardiovascular risk factors. 4 Postoperative atrial fibrillation (PoAF) is an important problem that increases mortality and morbidity rates after cardiac surgery operations. 5 Various studies have been conducted on the relationship between vitamin D and PoAF.…”
Section: Commentarymentioning
confidence: 99%
“…In a study, it was revealed that the risk of hospitalization and mortality increased due to vitamin D deficiency in patients with heart failure 3 . The effects of vitamin D deficiency on atrial fibrillation (AF) are explained by direct effects on atrial tissue and indirect effects on cardiovascular risk factors 4 …”
Section: Commentarymentioning
confidence: 99%
“…Vitamin D 3 deficiency or insufficiency is a highly prevalent but often underestimated condition in the general population, especially among the elderly [ 1 , 2 ]. Over the last two decades, several studies have demonstrated a negative impact of vitamin D 3 deficiency on morbidity and mortality in various patient populations with chronic illnesses [ 3 , 4 , 5 , 6 ], and associations between vitamin D 3 deficiency and cardiovascular diseases have been reported (reviewed in [ 7 , 8 ]). By targeting the vitamin D 3 receptor expressed on cardiomyocytes, vitamin D 3 has been found to affect myocardial metabolism with beneficial effects on myocardial dysfunction and cardiac hypertrophy [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%